PENGUATAN KAPASITAS GURU DALAM PENGELOLAAN KESEHATAN DAN LINGKUNGAN SEKOLAH MELALUI EDUKASI GEMA CERMAT DAN PELATIHAN KOMPOSTING DI SMK NEGERI 6 DENPASAR - Anak Agung Gede Indraningrat; Made Dharmesti Wijaya; I Gede Sutapa (Jurnal Abdi Insani, 2026)
SMK Negeri 6 Denpasar is a public vocational high school that still requires strengthening in school health and environmental management aspects. Initial observations and discussions with the school identified several major issues, including the suboptimal function of the School Health Unit (UKS), limited health literacy regarding rational drug use, the absence of routine health screening for teachers, and conventional organic waste management practices. This community service program aimed to improve teachers’ capacity in integrated and sustainable school health and environmental management. The implementation methods included socialization, GEMA CERMAT education, teacher health screening, composting training, and periodic monitoring and evaluation. The service team also provided supporting facilities, including basic health equipment, UKS supplies, an organic waste shredding machine, composting bags, compost microbial starter, waste bins and family medicinal plants (TOGA). The results showed that the program was implemented successfully and received positive responses from the participants. Pre-test and post-test results from 32 participants demonstrated an increase in the average score from 62 to 79 after the evaluation. Monitoring and evaluation further indicated that teachers were able to independently manage composting activities, optimize the use of UKS facilities, and improve the school environment through the development of TOGA and ornamental plant gardens. This program is expected to support the establishment of a healthy and environmentally sustainable school culture.